Hak Politik Perempuan dalam Perspektif Islam (Politics Rights of Women in Islamic Perspective) - Suhairi, Suhairi (ISTINBATH JURNAL HUKUM, 2004)
Islam declarates that male and female are equals. Islam gives to women syariâat rights, humanity rights including politics rights. As a reality, those rights have not comforted fully by females. Part of muslim community including the leaders of Islam have still opinions that females do not have authorities in politics public affairs. That is based on verses which are interpreted as gender pseudo. Politics rights in Islamic perspective are right in suggesting an opinion (voice) in General Election and taking of a vote with all shorts of kinds. Either right of nomination tobe a member of delegation institutes or local institutes. Rights of nomination tobe a president (head state)Keywoerds : Politics Rights, Islamic Perspective